Close to home - Robinson, Peter, 1950- (New York : William Morrow, 2003)
Unable to forgive himself for his possible role in the disappearance of a childhood friend, Detective Inspector Alan Banks finds himself confronting the unsolved case thirty-five years later when his friend's body is discovered.
Keywords: Banks, Alan (Fictitious character) -- Fiction; Police -- England -- Yorkshire -- Fiction; Missing persons -- Fiction; Male friendship -- Fiction; Yorkshire (England) -- Fiction; Mystery fiction